‘Well I don’t feel that’: schemas, worlds and authentic reading in the classroom - Giovanelli, Marcello; Mason, Jessica (Wiley, 2015)
This article explores reading in the English classroom through a cognitive linguistic lens. In particular, we consider how students’ ability to engage with a text, which we term authentic reading, can be facilitated or restricted. We draw on two case studies featuring Year 7 students working with the novel Holes (Sachar 2000), and the short story ‘The man who shouted Teresa’ (Calvino 1996) respectively, and argue for the benefits of using cognitive linguistics as a tool for teachers and researchers to ‘think with’ when considering reading in the classroom.